The Impact of Indonesia’s National Health Insurance on Healthcare Utilization Among the Elderly: A Decade of Implementation - Verdiana, Antokalina Sari (Riviera Publishing, 2026)
Indonesia's elderly population (aged 60+) now exceeds 7% of the total population, creating challenges for equitable health service delivery. The National Health Insurance (JKN) program, supporting SDG 3.8, has achieved 98% population coverage over its decade-long implementation. Longitudinal Susenas survey data were used to evaluate the utilization of healthcare services among older individuals by examining their use over time and correlating it with relevant factors, which were categorized into potential predictors as defined by the Andersen model, based on demographic, socioeconomic, and healthcare need indicators. Logistic regression was conducted, and propensity score matching with a caliper of 0.05 was used to ensure statistical rigor in the study. Furthermore, the impact of JKN membership on healthcare consultations was estimated over the past decade using a difference-in-differences method. Factors influencing JKN enrollment shifted over the decade, with education and urban residence becoming more important, while internet access and health-related factors declined. JKN membership was not significant in 2013 but became significant by 2023, with a 7.71% average treatment effect. Difference-in-differences analysis shows a 5.85% increase in healthcare utilization attributable to JKN. JKN has produced modest gains in elderly healthcare utilization (5.85%). Further progress requires addressing quality perceptions and geographic inequities to achieve universal health access for Indonesia's aging population.